Love Your Heart: Edukasi Gagal Jantung Kongestif untuk Generasi Muda di SMKN 11 Bandung - Budi Rustandi; Theophylia Melisa Manumara; Adinda Putri Eryana; Annisa Bintang; Desti Alfiana; Dwi Mayangsari; Dwi Varetta Maharani; Kurniawan Kurniawan; Meri Oktapia Suci Rahmadani; Nabila Zalfa; Priska Priska; Salwa Fadhila Oktaviani Solihin; Vina Alvionita; Zahra Alifannisa (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Congestive Heart Failure is a condition characterized by the heart's inability to pump blood effectively, leading to symptoms such as shortness of breath and leg swelling. The primary causes include hypertension and coronary artery disease, which can be prevented through a healthy lifestyle from a young age. Public knowledge, especially among adolescents, regarding risk factors and early signs of CHF remains low, making health education crucial to increase awareness and promote early prevention. The study search was conducted using online sources such as PubMed and Google Scholar to gather data related to the mechanisms, prevention strategies, and healthy lifestyle practices to enhance awareness and prevent the progression of CHF. The conclusion indicates that continuous education and improved access to information can enhance adolescents' understanding of CHF and encourage healthy behaviors that contribute to disease prevention in the future.